Leadership and organizational commitment in teacher training universities in Iran: The moderating role of emotional intelligence / Alireza Tahernejad - Alireza, Tahernejad (2016)

(untitled)
In this highly competitive and globalized world, organizations often reach for effective leaders to bring changes and move the organization to a better future. There is a widely accepted belief amongst both academics and practitioners that effective leaders can be one of the primary causes of the success in organizations through enhancing several important factors that directly and indirectly determine the organizations’ prosperity in this ever changing environment. One of the significant outcomes of effective leadership is followers’ organizational commitment. Having committed employees can subsequently lead to efficiency and productivity in organizations. Different leadership styles have been proposed and examined to positively influence subordinates’ organizational commitment. In efforts to maximize leadership effectiveness, scholars believe that moving from transactional-transformational to spiritual leadership continuum can lead to the enhancement of organizational commitment. Further, research points to the significant role emotional intelligence plays in the effectiveness of leadership, which needs additional insights in particular from non-western contexts. To respond to the limited attention directed to the empirical investigation of the above notions, this research set out to address this gap in the current body of leadership literature. Specifically, three leadership styles (transactional, transformational, and spiritual) were focused on this research to examine their influence on employee organizational commitment. In addition, leaders’ emotional intelligence as a moderator of leadership-commitment link was investigated. The proposed relationships were examined in a relatively understudied context, Iran, while focusing on one of the higher education sectors, Teacher Training Universities responsible to train and educate personnel to be recruited as teachers in schools. Collecting data from both employees and leaders of this specific higher education sector, the hypotheses advanced in this research were examined. Results indicate that the three leadership styles including iv transactional, transformational, and spiritual leadership were positively related to employee organizational commitment. As proposed, spiritual leadership style, through spiritual well-being, found to have the highest impact on employee organizational commitment. Further, leaders’ emotional intelligence was found to moderate the leadership-commitment link. Leaders with higher emotional intelligence were found to more positively influence organizational commitment among their employees. In other word, the higher the leaders’ emotional intelligence, the stronger the leadershipcommitment link.